Recentralization in China? - Ahmad, Ehtisham (IMF Working Papers; Working Paper ;, 2002)
The paper assesses the changing nature of the relations between the provinces and the central government in China during the 1990s. It examines the fiscal reforms initiated in 1994 and subsequent developments. The expenditure needs of the center and the richer provinces are juxtaposed against the need for "redistribution" to the more backward regions.